2013
DOI: 10.4236/jct.2013.49a002
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Chemotherapy as a Multimodal Treatment for Gastric Cancer Patients with Peritoneal Metastasis

Abstract: Peritoneal metastasis of gastric cancer is mainly caused by the dispersion of free cancer cells from the serosal surface of the invaded stomach, from surgically transected lymphatic channels, and from tumor cell-containing blood from the primary lesion into the peritoneal cavity. Intraperitoneal chemotherapy (IPC) combined with surgery has performed for the prevention and treatment of peritoneal metastasis in gastric cancer. The efficacy of this technique is influenced by the pharmacokinetic advantage achievab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Peritoneal dissemination, the most frequently observed metastatic pattern of gastric cancer, is a critical indicator of poor patient prognosis, and is the main contributor to the failure of radical gastrectomy in patients with advanced gastric cancer (2,3). Despite developments in systemic and intraperitoneal chemotherapy, only a minority of patients with advanced disease respond to treatment (4)(5)(6)(7)(8), indicating the need for novel strategies, in addition to conventional surgery and chemotherapy, to treat this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dissemination, the most frequently observed metastatic pattern of gastric cancer, is a critical indicator of poor patient prognosis, and is the main contributor to the failure of radical gastrectomy in patients with advanced gastric cancer (2,3). Despite developments in systemic and intraperitoneal chemotherapy, only a minority of patients with advanced disease respond to treatment (4)(5)(6)(7)(8), indicating the need for novel strategies, in addition to conventional surgery and chemotherapy, to treat this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IPC using MMC can induce encapsulated peritoneal fibrosis because of its chemical toxicity. 9 In contrast, as taxanes are hydrophobic and have high molecular weights, they are retained much longer in the peritoneal cavity. 16 , 17 IPC cannot achieve reduction of PM in only a few times, whereas taxane-based IPC can be administered repeatedly without peritoneal adhesion because of its antifibrotic effect.…”
Section: Discussionmentioning
confidence: 99%
“… 6 8 PM is relatively resistant to systemic CTX because of the poor blood supply and hypoxia of cancer cells in the peritoneum. 9 Therefore, intraperitoneal chemotherapy (IPC) has been theoretically acceptable as regional intensive CTX to treat PM. Several studies have reported the effectiveness of taxane-based IPC for PM of GC, but its effectiveness in SGC has not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, early administration of locoregional cytotoxic therapy with known pharmacokinetic advantages over IV chemotherapy may reach tumour cells prior to metastatic implantation. Reaching tumours prior to the development of cellular resistance-mediating pathways is known to yield improved efficacy [26][27][28]. Clinically, this strategy has been demonstrated to yield improved survival with the addition of IP chemotherapy in optimally debulked stage-III ovarian cancers [29].…”
Section: Introductionmentioning
confidence: 99%